2022
DOI: 10.1038/s41598-021-04661-2
|View full text |Cite
|
Sign up to set email alerts
|

Live imaging of micro and macro wettability variations of carbonate oil reservoirs for enhanced oil recovery and CO2 trapping/storage

Abstract: Carbonate hydrocarbon reservoirs are considered as potential candidates for chemically enhanced oil recovery and for CO2 geological storage. However, investigation of one main controlling parameter—wettability—is usually performed by conventional integral methods at the core-scale. Moreover, literature reports show that wettability distribution may vary at the micro-scale due to the chemical heterogeneity of the reservoir and residing fluids. These differences may profoundly affect the derivation of other rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…At least 10 drops of DI water were placed in random positions on the surface of each core plate, and the CA was measured after equilibration. The contact angle value was calculated as an average mean, and the standard deviation was determined. , …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…At least 10 drops of DI water were placed in random positions on the surface of each core plate, and the CA was measured after equilibration. The contact angle value was calculated as an average mean, and the standard deviation was determined. , …”
Section: Methodsmentioning
confidence: 99%
“…The contact angle value was calculated as an average mean, and the standard deviation was determined. 10,65 2.2.6. ζ-Potential Measurements. The methodology was developed based on Ding and Rahman 66 and Lara Orozco et al 67 To prepare a calcite suspension, 10 mL of brine/surfactant solution was placed into a 20 mL vial, and 0.1 g of rock powder was added.…”
Section: Interfacial Tension Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in [38], it was shown that the wettability of carbonates measured by a common laboratory method (contact angle) that differs from wettability measured in corresponding areas of the surface at the microlevel. As such, results demonstrated that wettability at the microlevel was mixed (i.e., hydrophilic and hydrophobic zones) while at the macrolevel surface showed only hydrophobic wetting preferences.…”
Section: Wettability Of Formation Rocks Its Modification and Measurin...mentioning
confidence: 99%